Migration-adsorption mechanism of metallic impurities out of chemically amplified photoresist onto silicon-based substrates - Yang, CC; Ko, FH; Wang, MY; Wang, TK; Wu, SC (My University, 2000)
The radioactive tracer technique was applied to investigate the migration and adsorption behaviors of metallic impurities (i.e., Ba, Cs, Zn, and Mn) out of chemically amplified photoresist onto silicon-based underlying substrates. Two important process parameters, i.e., baking temperatures and substrate types (e.g., bare silicon, polysilicon, oxide, and nitride) were evaluated. Our results indicated that the transition metals (Zn and Mn) have lower migration ratios than alkali metal (Cs) and alkaline earth metal (Ba), irrespective of the substrate types and baking temperatures. The transition metals form stable complexes with the coexisting solvents and/or hydrolysis species in the photoresist layer. The size of the metal complex, the drag force in solvent evaporation, and the baking process were found to have significant effects on impurity migration. A new model, together with the metal migration in the chemically amplified photoresist and the subsequent adsorption onto the underlying substrate, was proposed to explain the pathway of the metal migration. This model could explain the migration ratios of metallic impurities out of the photoresist layer onto the substrate surface. (C) 2000 The Electrochemical Society. S0013-4651(00)01-026-0. All rights reserved.